Pengaruh Efikasi Diri dan Kecerdasan Logis Matematis terhadap Prestasi Belajar Matematika - Mubaroh, Lutfiah; Somawati, Somawati (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to determine whether there is an influence between self-efficacy and logical-mathematical intelligence on mathematics learning achievement. The research method used is a survey method with a quantitative approach. The sample consists of 40 eighth-grade students from SMP Negeri 2 Sepatan Timur in Tangerang Regency, selected using simple random sampling. Instrument testing was conducted with a sample of eighth-grade students from SMP PGRI 3 Larangan in Tangerang City. The linearity test for  with Y indicates that the data is linear. Similarly, the linearity test for  with Y also shows that the data is linear. The multicollinearity test for  and  indicates that there is no multicollinearity. Therefore, correlation and regression analysis can be continued with parametric statistical data. The results of the study conclude that there is a positive influence between self-efficacy and logical-mathematical intelligence together on mathematics learning achievement